Management of Distal Left Main Coronary Artery Aneurysm - Ko, Po-Yen; Chang, Chih-Ping; Lin, Jen-Jyh; Liu, Juhn-Cherng (The Thoracic and Cardiovascular Surgeon, 2013)
Aneurysms of the left main coronary artery are extremely rare. The cause of such aneurysms is uncertain. Although the treatment of distal left main aneurysms is very complicated, definitive treatment is necessary because the aneurysm may grow further and cause embolism or rupture. Herein, we report a case of acute myocardial infarction caused by aneurysm of the distal left main coronary artery, which was successfully treated by performing coronary artery bypass surgery, followed by implantation of a polytetrafluoroethylene-covered stent.
Keywords: left main coronary artery aneurysm; polytetrafluoroethylene-covered stent; coronary artery bypass surgery